Relatos de pacientes con alimentación Enteral sobre el cuidado enfermero. Area Gastroenterológica Hospital Abel Gilbert Pontón periodo abril septiembre 2019 - Lombeida Arboleda, Dalila Dayana (2019)
Introduction: Nursing goes beyond being a profession, it is a vocation focused on patient care, instilled in the principles, values, respecting and enforcing human rights, these being the foundations to guarantee satisfaction in the quality of care. Purpose: To reveal stories of patients with enteral feeding regarding the care provided by the nursing professional through the in-depth interview, to improve the quality of life of the patient in the Gastroenterology Area of the Abel Gilbert Pontón Specialty Hospital. Guayaquil April-September 2019 period. Methodology: The research is of a qualitative type using the case study as a design with the application of the phenomenological approach, 19 questions were developed for the application of the in-depth interview to the patients of the Gastroenterology service, using the non-probabilistic sampling for convenience, for the respective analysis of the information, it was transcribed to the Atlas Ti program where a hermeneutical unit consisting of 6 objects was constructed: DPS, appointments, code, memos and networks, obtaining a complete analysis of all the interviews that were applied to patients with enteral feeding. Results: The patients identify the nursing assistant without a hat and the nursing graduate with a hat, also by the name put on the apron of the uniform and by their different activities, most of the patients express that they take good care of them, they treat with Respect, patience, empathy, consideration emphasizing the gratuity of the same, however, the remaining part states that they are dissatisfied with their work, the nursing team allows family members to participate as support in food care Enteral, half of the patients interviewed appreciate nursing care as of medium quality, suggest they come to the call; The experience of patients with enteral feeding is reflected by feelings of fear, anguish, pain, discomfort, discomfort, also by thoughts such as adopting a change in attitude in their lifestyle. Conclusions: In the Gastroenterology service, the majority of patients prefer to verify the information provided by the nursing professional regarding their health status with the attending physician, the majority also mention that the nursing professional attends them well and prior to the procedures apply biosecurity and hygiene measures. Keywords. Nursing care, patients, enteral feeding, categories